Towards a Carbon Nanotube Intermodulation Product Sensor for Nonlinear Energy Harvesting. (25th May 2015) - Lerner, Mitchell B.; Goldsmith, Brett; Rockway, John; Perez, Israel
Abstract : It is critically important in designing RF receiver front ends to handle high power jammers and other strong interferers. Instead of blocking incoming energy or dissipating it as heat, we investigate the possibility of redirecting that energy for harvesting and storage. The approach is based on channelizing a high power signal into a previously unknown circuit element which serves as a passive intermodulation device. This intermodulation component must produce a hysteretic current-voltage curve to be useful as an energy harvester. Here we demonstrate a method by which carbon nanotube transistors produce the necessary hystereticI -V curves. Such devices can be tailored to the desired frequency by introducing functional groups to the nanotubes. These effects controllably enhance the desired behavior, namely, hysteretic nonlinearity in the transistors'I -V characteristic. Combining these components with an RF energy harvester may one day enable the reuse of inbound jamming energy for standard back end radio components.